2016
DOI: 10.1002/14651858.cd006663.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme replacement therapy for Anderson-Fabry disease

Abstract: Trials comparing enzyme replacement therapy to placebo show significant improvement with enzyme replacement therapy in regard to microvascular endothelial deposits of globotriaosylceramide and in pain-related quality of life. There is, however, no evidence identifying if the alfa or beta form is superior or the optimal dose or frequency of enzyme replacement therapy. With regards to safety, adverse events (i.e., rigors, fever) were more significant in the agalsidase beta as compared to placebo. The long-term i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 83 publications
0
58
0
6
Order By: Relevance
“…The Cochrane review with similar eligibility criteria retrieved studies up to September 2015 [7]. Using Medical Subject Headings (MeSH) based on the terms “Fabry Disease,” “agalsidase alfa,” and “agalsidase beta” (S1 Table) we replicated the search strategy of that review [7] for Medline, EMBASE, and LILACS from October 1, 2015 to March 1, 2016.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cochrane review with similar eligibility criteria retrieved studies up to September 2015 [7]. Using Medical Subject Headings (MeSH) based on the terms “Fabry Disease,” “agalsidase alfa,” and “agalsidase beta” (S1 Table) we replicated the search strategy of that review [7] for Medline, EMBASE, and LILACS from October 1, 2015 to March 1, 2016.…”
Section: Methodsmentioning
confidence: 99%
“…A Cochrane review [7] of nine randomized controlled trials (RCTs) addressing patient-important outcomes and including 351 patients reported that ERT is associated to significant improvement of endothelial deposits of globotriaosylceramide and of pain-related quality of life compared to placebo; however the effects of ERT on patient-important outcomes related to AFD was still unclear. In this regard, RCTs enrolled a limited number of patients and follow-up was relatively short, frequently just a few months.…”
Section: Introductionmentioning
confidence: 99%
“…Ein jüngster Review der Cochrane Collaboration zum Thema Enzymersatztherapie bei M. Fabry konnte aufgrund der Qualität der erhobe- nen Daten nur 6 klinische Studien mit insgesamt 223 Patienten auswerten. Die Autoren kamen zu dem Schluss, dass aufgrund der limitierten Ergebnisse der qualitativ eingeschränkten Studien wissenschaftlich belastbare Ergebnisse für die Wirksamkeit der ERT bei M. Fabry bisher fehlen [33] …”
Section: Diskussionunclassified
“…In light of the availability of disease-modifying therapies, specifically enzyme replacement therapy, there is increasing pressure to be able to identify functionally significant variation in the alpha galactosidase gene rather than wait for documentation of histological involvement of target organs. 9 The situation is further complicated by the increasing recognition (although with variable rigor) of clinically significant involvement of female heterozygotes, presumably through partially dominant mechanisms or tissue specific X-inactivation. 10 Although the simple plasma or urine levels of Gb3 have been shown not to vary between affected and unaffected carriers of bona fide mutations, a degradation product of Gb3, specifically lyso-Gb3 has been hypothesized as a potential discriminant between those with disease and simple mutation carriers.…”
Section: New Functional Assaysmentioning
confidence: 99%